Microeconomics : optimization, experiments, and behavior - Burkett, John P. (OUP E-Books., 2006)
Covering research in behavioral and experimental economics, this research documents behavior inconsistent with some elements of traditional theory. Topics covered include studies of loss aversion, reference-dependent preferences, the context and framing of choice, hyperbolic discounting and inconsistent intertemporal choice, and more.